Analisis Literatur Pemanfaatan Media Video Pembacaan Puisi bagi Pengembangan Ekspresi Peserta didik SD - Ramadhan Putra Pamungkas; Mella Tia Tristanti; Maharani Dwi Wahyu Nindiasari; Panji Adi Nugraha; Bayu Purbha Sakti (CV. ITTC INDONESIA, 2025)
This study is a literature analysis aimed at mapping empirical and conceptual evidence regarding the use of poetry reading videos to develop elementary school students' expressive abilities. The review includes studies published between 2020 and 2025, including journal articles, proceedings, theses, and media development reports. The synthetic results indicate that poetry reading videos serve as expressive models (intonation, articulation, mimicry, tempo), increase student motivation and engagement, and help build self-confidence when performing. Furthermore, videos provide multimodal access that facilitates understanding of poetry meaning and reading techniques. Findings from several experimental and media development studies support the effectiveness of video-based interventions for expressive aspects of poetry reading in elementary school children. Recommendations are provided for the planned integration of videos as part of instructional design, teacher training, and further research combining quantitative and qualitative measurements